L’usage du territoire. Dans la banlieue de Paris, un itinéraire de Denis Moreau à la manière de Jean‑Yves Petiteau - Xavier Dousson; Sandra Parvu (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Following Jean-Yves Petiteau’s method, Denis Moreau, the architect and founder of banlieuedeparis takes us on a journey through the southern Parisian suburbs of Gentilly, Arcueil, Kremlin-Bicêtre, and Villejuif. During this walk, he tells us about his use, observations, method, and understanding of a territory that he has meticulously and tirelessly explored for almost thirty years.